School Administrators’ Possession of Digital Skills and Digital Literacy Content for Implementation of Digital Literacy Program in Public Primary Schools in Kitui County-Kenya - Wambua, Esther; Kisirkoi, Florence; Maithya, Paul (Journal of Education and Practice, 2023)
Purpose: The purpose of this study was to find out school administrators' possession of digital skills and digital literacy content impact on the implementation of digital literacy program in public primary schools in Kitui county-Kenya. Methodology: Descriptive survey research design was used to describe the characteristics of the respondents. Review of related literature was done in line with the objectives of the study. The target population comprised of 3280 school administrators, who comprised of both head teachers and deputy head teachers and 328 classroom teachers making a total of 3608 respondents. A sample of 10% of the total population was taken making a sample size of 361 respondents, comprising of 328 school administrators and 33 classroom teachers. Self-administered questionnaires were used for data collection. A test- retest was carried out in four public primary schools to establish the reliability of the research instrument. Data collected were analyzed descriptively with help of Statistical Packages of Social Sciences (SPSS) version 28. Findings: The study established that school administrators' skills and competencies in digital technology were a good predictor of a smooth digital literacy implementation. On the overall the study found out that schools' administrators' possession and use of digital literacy skills was below average. The study further established that 145(88.48%) respondents could access digital literacy content in their school while 19(11.52%) could not access the content in school. Unique Contribution to Theory, Policy and Practice: The findings of the study will guide the leadership in effective delivery of flagship programs like the digital literacy program through multi-agency approaches